ANALISA PERANCANGAN SISTEM INFORMASI PERIZINAN TINGGAL ORANG ASING DI INDONESIA BERBASIS WEBSITE (STUDI KASUS: PT. PURI JAYA) - Rezky Arianda; Angga Yudi Pratama; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Every Foreigner who will enter, cross in and out of the Indonesian Territory, as well as be and have activities in Indonesia, must follow and comply with all laws and regulations of the State of Indonesia. PT. Puri Jaya is a company engaged in providing immigration document licensing services for foreign nationals who need legal documents to stay in Indonesia. At this time PT. Puri Jaya is not widely known by foreigners, because it does not yet have an information system in the form of a website. The purpose of this study is to develop a web-based information system for permitting foreigners to stay in Indonesia in order to provide better services. The application was developed using the Rapid Application Development (RAD) method and structured analysis modeling, this system was created using the PHP programming language and MySQL database. The results of this study are the system can provide convenience in order to find out the requirements for residence permits for foreign citizens, input foreigner data, upload passports, verify foreigner data by admin, visit stay permits, limited stay permits quickly and effectively.